Cocaine-Induced Ventilation/Perfusion Mismatch Mimicking Pulmonary Embolism. (February 2020) - Surapaneni, Phani Keerthi; Abe, Temidayo; Fas, Norberto
Pulmonary complications from cocaine use can range from bronchospasm to vasospasm leading to pulmonary infarction. Profound vasospasm may also lead to perfusion defects presenting as pulmonary embolism on ventilation-perfusion scan. A 65-year-old patient with a past medical history of substance abuse and chronic kidney disease presents to the emergency department with sudden-onset chest pain and shortness of breath. Ventilation-perfusion scan revealed filling defect most notably in the lingual lobe. He was later discharged on warfarin for the management of pulmonary embolism. The patient presented to the emergency department 2 weeks later with similar complaints; the international normalized ratio was subtherapeutic, and urine drug screen was positive for cocaine. Repeat ventilation-perfusion scan revealed no filling defects. Follow-up bilateral venous Doppler of lower extremities and D-dimer were within normal limits.